Enhancing Orientation and Mobility Skills in Learners who are Blind through Video gaming - Sánchez, Jaime (Creat Cognit, 2013)
In this work we present the results of the cognitive impact evaluation regarding the use of Audiopolis, an audio and/or haptic-based videogame. The software has been designed, developed and evaluated for the purpose of developing orientation and mobility (O&M) skills in blind users. The videogame was evaluated through cognitive tasks performed by a sample of 12 learners. The results demonstrated that the use of Audiopolis had a positive impact on the development and use of O&M skills in school-aged blind learners.